The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.06.03.20117994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ozone therapy for patients with COVID-19 pneumonia: a Quasi-Randomized Controlled Trial

Abstract: Importance Aside from supportive management, there remains no specific treatment for Coronavirus Disease 2019 (COVID-19). Objective: Determine whether ozonated autohemotherapy is associated with a shorter time to clinical improvement in patients with severe COVID-19 pneumonia. Design: Single-center proof-of-concept prospective cohort study. Setting: Internal Medicine ward at Policlinica Ibiza Hospital, Spain. Participants: Eighteen consecutive patients with laboratory confirmed COVID-19 infection and severe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Ozone has virtually no side effects and does not induce microbial resistance patterns like pharmacologic therapies [267]. Numerous studies affirm ozone's efficacy and safety in Covid-19 disease [267][268][269][270][271][272][273][274][275][276][277][278][279][280][281]. Thorp et al describe mechanisms by which ozone therapy affects Covid-19 outcomes: increased antioxidant production, induction of Nrf2-and HO-1-mediated nuclear mechanisms, down-regulation of pro-inflammatory immune pathways, direct toxic viral effects, inhibition of viral replication and increased blood and tissue oxygenation [279].…”
Section: The Case For Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Ozone has virtually no side effects and does not induce microbial resistance patterns like pharmacologic therapies [267]. Numerous studies affirm ozone's efficacy and safety in Covid-19 disease [267][268][269][270][271][272][273][274][275][276][277][278][279][280][281]. Thorp et al describe mechanisms by which ozone therapy affects Covid-19 outcomes: increased antioxidant production, induction of Nrf2-and HO-1-mediated nuclear mechanisms, down-regulation of pro-inflammatory immune pathways, direct toxic viral effects, inhibition of viral replication and increased blood and tissue oxygenation [279].…”
Section: The Case For Ozonementioning
confidence: 99%
“…Ozone therapy reduced viral titers and improved clinical symptoms in Covid-19-infected ICU patients [280]. Other studies found that ozone shortened time-lines for clinical improvement [281]. Since ozone confers protection against organ-injury in ischemia-reperfusion injury it only stands to reason that it should prevent or mitigate multi-system organ failure associated with advanced Covid-19 infection if administered in a time-sensitive manner.…”
Section: The Case For Ozonementioning
confidence: 99%
“…Oxygen/ozone therapy (another treatment known to promote antioxidant response) has also been proposed to help protect against ischemia‐reperfusion injury and other pathological manifestations of severe CoVID‐19 [302] . Some reports on small cohorts of patients have reported numerical, but not statistically‐significant effects of ozone on CoVID‐19; [302] others, with similarly small numbers of people have reported positive effects [303] …”
Section: Other Hypothesesmentioning
confidence: 99%
“…301 Some reports on small cohorts of patients have reported numerical, but not statistically-significant effects of ozone on CoVID-19; 301 others, with similarly small numbers of people have reported positive effects. 302 A recent study showed numerous pathways rewired upon CoVID-19 infection, including processing mRNA and several metabolic elements, including nucleic acid metabolism pathways. Inhibition of proteins identified in such pathways (albeit often by compounds not in clinical use) appeared to inhibit viral proliferation, although the effects on host cells were not thoroughly investigated.…”
Section: Targeting Infection and Harnessing Fortuitous Antiviral Effementioning
confidence: 99%